The Effect of SQ4R Method to the Improvement of Critical Reading Comprehension - Magvirah Octasary; Nurhaida Lakuana (BABASAL English Education Journal, 2023)
This research aims at proving that the use of SQ4R method improves the critical reading ability of the grade XI MIA of MAN 1 Sausu. The method used in this research was quasi-experimental research design. The sample of the research was selected by using purposive sampling technique, in which the researcher intentionally chose grade XI MIA 2 as experimental class and XI MIA 4 as control class. The instruments of data collection were questionnaire items, interview items and tests. The data were analyzed by using t-test statistical and descriptive methods. Based on the results of the tests, the mean score of the experimental class is 80.38, while the mean score of the control class is 71.  Furthermore, based on the result of questionnaire, there were 96% students decided the implementation of SQ4R method had given contribution to improve their thinking and reading critical ability, then considered that the practice of SQ4R method was very effective for them. In other words, applying SQ4R method affects students’ critical reading comprehension of the grade XI MIA of MAN 1 Sausu